O protagonismo das mulheres dos projetos de assentamentos localizados na mesorregião do Triângulo Mineiro: luta por efetivação de direitos ? - Kamimura, Ana Lúcia Martins [UNESP] (2014)
The subject of this research is the women's protagonism in Settlement Projects (PAs) located in mesoregion of Triângulo Mineiro. For that reason searching from a critical analysis of those settlements' reality, how materializes as the rural woman/worker protagonism because of their active participation during the resistance and struggle for land that is recognized as a social right. To accomplish this goal, based on a critical analysis of reality and considering this reality from an entire perspective, seeking to understand the protagonism of rural women workers observing the Brazilian's land distribution issues that disregards the importance of understanding land reform as a development policy. In this regard, bibliographic and documentary research were used, having as parameter studies done in the light of dialectical and historical materialism. Additionally, though the technique of oral history, proceeding from information portrayed in the life stories of eleven women who are linked to Pas Paulo de Faria, Canudos, Olhos D'Água, Flávia Nunes, Emiliano Zapata, Irmãos Naves, Valcy dos Santos and Dom José Mauro, all located in the Greater Region of Triângulo Mineiro. The elements of analysis in the stories of each women were their origins, memories of childhood, education level, their integration into the world of wage labor, the struggles within the Movement, the condition as woman and their protagonism in areas of struggle to ensure their right of achieve the land. Based on the analysis of all these elements present in their stories, it was possible to understand that despite the proven protagonism of these women in areas of struggle and its importance to the success of any endeavor whitin the PAs, as well as the progress made regarding the condition of women inside the social movements struggling for land. It still need to keep in constant struggle to be recognized their competence...